Stigma and posttraumatic growth among COVID-19 survivors during the first wave of the COVID-19 pandemic in Malaysia: a multicenter cross-sectional study - Azman, Nazirah; Nik Jaafar, Nik Ruzyanei; Leong Bin Abdullah, Mohammad Farris Iman; Abdul Taib, Nur Iwana; Mohamad Kamal, Nurul Ain; Abdullah, Muhammad Najib; Dollah, Siti Nordiana; Mohamed Said, Mohd Shahrir (Frontiers in Psychiatry, 2023)
Abstract - Background: COVID-19 infection can cause negative and distressing psychological sequelae, but traumatic stressors may also facilitate the development of positive psychological change beyond one’s previous level of adaptation, known as posttraumatic growth (PTG). Current studies mainly focused on the negative effects of COVID-19 infections on mental health. Data on PTG among patients recovered from COVID-19 remains limited. This study aimed to evaluate the level of posttraumatic growth and its associations with stigma, psychological complications and sociodemographic factors among COVID-19 patients after six months of post hospitalization. Method: A cross-sectional online survey was conducted on 152 COVID-19 patients after six months discharged from Hospital Canselor Tuanku Muhriz, MAEPS Quarantine Centre, and Hospital Sungai Buloh, Malaysia. They completed a set of questionnaires on sociodemographic and clinical data, Posttraumatic Growth Inventory (PTGI-SF) to assess the level of PTG, Kessler Psychological Distress (K6) to measure the degree of psychological distress, General Anxiety Disorder-7 (GAD-7) to evaluate the severity of anxiety symptoms, Patient Health Questionnaire (PHQ-9) to assess the severity of depression symptoms, and Explanatory Model Interview Catalogue Stigma Scale (EMIC-SS) to record the degree of perceived stigma on COVID-19. Results: The median PTGI SF score of the respondents was 40.0. (Interquartile range 16.0). Multivariable general linear model with bootstrapping (2000 replications) revealed the factors which significantly predicted PTG were higher level of perceived stigma score (B = 0.367, 95% CI =. 0.041 to 0.691, p = 0.026), Malay ethnicity (B = 12.767, 95% CI = 7.541 to 17.993, p < 0.001), those who have retired (B = -12.060, 95% CI = -21.310 to -2.811, p = 0.011) and those with history of medical illness (B = 4.971, 95% CI = 0.096 to 9.845, p = 0.046). Conclusion: Experiencing stigma contributed to one’s PTG in addition to psychosocial factors such as ethnicity, history of medical illness and retirement.